Papillary Cystadenoma of the Testis - Fidelis, Otobo O.; Edet, Ikpi; Glen, Enakirerhi; Edoise, Isiwele M.; Ayodele, Omotosho; Akanimo, Essiet; Ekwere, Paul D; Nkposong, Edet O (Medical Science: Trends and Innovations Vol. 10, 2025)
Papillary cystadenomas are common benign tumors usually found in post-pubertal males. More commonly seen are unilateral cases, but bilateral cases also occur especially in patients previously diagnosed with von Hippel-Lindau (VHL) disease. Histologically, they can mimic metastatic renal cell carcinomas. Therefore, good clinical, radiological and histological analysis of cases is essential for appropriate treatment. Papillary cystadenomas are usually treated with simple excision. This is a report of a 24-year-old male undergraduate with a 3-month history of mildly tender right testicular swelling histologically diagnosed as papillary cystadenoma. Testicular ultrasound scans of the patient revealed slight probe tenderness and a bulky right epididymis measuring 13.7 mm × 15.6mm with a nodular hypoechoic area measuring 11.9 mm × 13.9 mm in size. The patient was requested to obtain an abdominopelvic ultrasound and brain CT scans for follow-up but was lost to follow-up. The early recognition and management of this tumor may help prevent possible late malignant transformation and also pave the way for the early identification of more pathologic entities like VHL and its associated lesions.